Synergy and Disruption: An Analysis of Fintech's Role in Digital Innovation and Increasing the Profitability of the National Banking Industry - Eva Tia Putri; Mansur Chadi Mursid (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2026)
Abstract The rapid development of financial technology (fintech) has significantly transformed Indonesia’s banking industry through technological innovation, service digitalization, and enhanced operational efficiency. This study aims to analyze the dual role of fintech—as both a synergy and a disruptor—toward banking performance and digital innovation. Findings from recent literature and empirical studies indicate that collaboration between banks and fintech firms, including the implementation of open banking, digital payment systems, and API-based services, improves service effectiveness, expands financial inclusion, and accelerates digital transaction growth. However, fintech penetration in payment services, digital lending, and retail financial products simultaneously creates competitive pressure on bank profitability, particularly through margin compression and shifts in consumer behavior. The study highlights that the impact of fintech is not uniform; instead, it is strongly influenced by banks’ strategic responses, digital readiness, and their ability to manage emerging risks and opportunities. This research contributes to a deeper understanding of the fintech–banking relationship and provides strategic recommendations for banks and regulators in navigating an increasingly competitive digital financial ecosystem. Keywords: Fintech, Digital Banking, Financial Innovation, Bank Profitability, Technological Disruption Abstrak Perkembangan teknologi finansial (fintech) telah mendorong transformasi signifikan dalam industri perbankan Indonesia melalui inovasi digital, integrasi layanan berbasis teknologi, serta peningkatan efisiensi operasional. Penelitian ini bertujuan menganalisis peran fintech sebagai kekuatan yang bersifat ganda, yaitu sebagai sinergi sekaligus disrupsi terhadap kinerja dan inovasi digital perbankan nasional. Studi literatur dan temuan empiris menunjukkan bahwa kolaborasi antara bank dan fintech, seperti implementasi open banking, digital payment, dan layanan berbasis API, mampu meningkatkan efektivitas layanan, memperluas inklusi keuangan, dan mendorong pertumbuhan transaksi digital. Namun, penetrasi fintech pada segmen pembayaran, pinjaman digital, dan layanan keuangan ritel juga memberikan tekanan kompetitif terhadap profitabilitas bank, terutama melalui penurunan margin keuntungan dan perubahan perilaku nasabah. Hasil penelitian menegaskan bahwa dampak fintech tidak bersifat tunggal, melainkan sangat bergantung pada strategi adaptasi, tingkat digitalisasi, serta kemampuan bank mengelola risiko dan peluang kolaborasi. Penelitian ini berkontribusi pada penguatan pemahaman mengenai hubungan fintech–perbankan serta memberikan rekomendasi strategis bagi bank dan regulator dalam menghadapi dinamika ekosistem keuangan digital yang semakin kompetitif. Keywords: Fintech, Digital Banking, Inovasi Keuangan, Profitabilitas Bank, Disrupsi Teknologi